Door-to-needle time in patients with acute myocardial infarction requiring thrombolytic therapy - Makgoale, Kgahlego Ramathabathe (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCur)--Stellenbosch University, 2015.